2021
DOI: 10.1016/j.celrep.2021.109163
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota regulates hypothalamic inflammation and leptin sensitivity in Western diet-fed mice via a GLP-1R-dependent mechanism

Abstract: Mice lacking a microbiota are protected from diet-induced obesity. Previous studies have shown that feeding a Western diet causes hypothalamic inflammation, which in turn can lead to leptin resistance and weight gain. Here, we show that wild-type (WT) mice with depleted gut microbiota, i.e., germ-free (GF) and antibiotic-treated mice, have elevated levels of glucagon-like peptide-1 (GLP-1), are protected against diet-induced hypothalamic inflammation, and have enhanced leptin sensitivity when fed a Western die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 55 publications
1
58
0
Order By: Relevance
“…EP3 blockade increased the overall Nrf2 protein signal in db/+ and db/db mice, and significantly increased the nuclear localization of Nrf2 in db/db mice ( Figure 6 A–A'). Analysis of the RNA-Seq data showed a strong upregulation of a set of canonical Nrf2 target genes ( Figure 6 C), including those with antioxidant functions ( Nqo1, Txn1, Gsr, Gclc, Gstm1 ), those involved in iron metabolism ( Ftl1 and Fth1 ), and those that produce NADPH ( Me1, G6pdx, Idh1 ) [ 17 ], while the expression of Keap1 , a negative regulator of Nrf2 [ 20 ], was decreased. In addition, the levels of 8-hydroxydeoxyguanosine (8OHdG), a marker of DNA damage, were significantly decreased in both db/+ and db/db mice after DG-041 treatment ( Figure 7 A–B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EP3 blockade increased the overall Nrf2 protein signal in db/+ and db/db mice, and significantly increased the nuclear localization of Nrf2 in db/db mice ( Figure 6 A–A'). Analysis of the RNA-Seq data showed a strong upregulation of a set of canonical Nrf2 target genes ( Figure 6 C), including those with antioxidant functions ( Nqo1, Txn1, Gsr, Gclc, Gstm1 ), those involved in iron metabolism ( Ftl1 and Fth1 ), and those that produce NADPH ( Me1, G6pdx, Idh1 ) [ 17 ], while the expression of Keap1 , a negative regulator of Nrf2 [ 20 ], was decreased. In addition, the levels of 8-hydroxydeoxyguanosine (8OHdG), a marker of DNA damage, were significantly decreased in both db/+ and db/db mice after DG-041 treatment ( Figure 7 A–B).…”
Section: Resultsmentioning
confidence: 99%
“…Sections were rehydrated and subjected to sodium-citrate-induced antigen retrieval. The primary antibodies used were: guinea pig anti-insulin (1:400; Dako #A0564, Carpinteria, CA), mouse anti-glucagon (1:500; EMD Millipore #MABN238, Bellerica, MA), rabbit anti-Ki67 (1:500; Abcam #ab15580, Cambridge, MA), rabbit anti-GLP-1R (1:500; Abcam #ab218532, validated on Glp1−/− tissue in [ 20 ]), or mouse anti-GLP-1R (1:30, DHSB mAb #7F38, validated on Glp1−/− tissue in [ 21 ]). Apoptosis was detected using an ApoAlert terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay kit according to the manufacturer's instructions (Clontech, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, circulating levels of the insulin-like growth factor-1 (IGF-1) were reported to regulate the astrocyte expression of several glutamatergic receptors and the production of eicosanoids, which ensure the optimal neurovascular coupling necessary for intense neuronal activity [113]. Furthermore, the gut microbiota, which can influence many neurological conditions (reviewed in [114]), was shown to release metabolites that tune astrocyte function directly, or through the perturbation of either microglia or meningeal natural killer cells [115][116][117][118][119]. For example, Rothhammer et al identified an anti-inflammatory effect of tryptophan metabolites, produced by Lactobacillus Reuteri and other ampicillin-sensitive gut bacteria [115], even though many aspects of this observation still need to be unraveled.…”
Section: Modulating Astrocyte Function By Tuning the Incoming Signalingmentioning
confidence: 99%
“…Also, calorie restriction was proposed to ameliorate the homeostatic functions of the astrocytes and to improve neuronal plasticity in the mouse hippocampus [121]. By contrast, a high fat, high sugar diet caused astrocytosis and enhanced neurotoxicity in a mouse model of spinal cord injury [119,122]. Finally, physical exercise [123][124][125] and environmental enrichment [123,126,127] importantly contributed to reduce reactive astrocytosis and alleviate the neuroinflammatory response in various animal models of injury and disease.…”
Section: Modulating Astrocyte Function By Tuning the Incoming Signalingmentioning
confidence: 99%
“…As we described before, neuroinflammation affects the CAN. Western diet induces inflammation of the hypothalamus, which in turn promotes leptin resistance and weight gain [ 120 ]. Notably, depletion of the GM in mice fed with HFD results in a diminished inflammation of the hypothalamus and improves leptin sensitivity [ 120 ].…”
Section: Role Of the Gut Microbiota In The Brain-heart Axis: Effect Of Metabolismmentioning
confidence: 99%